Pengaruh CR, ROA Dan PER Terhadap Harga Saham Pada Perusahaan Sektor Teknologi - Muhammad Kevin Adriansyah; Trisnadi Wijaya (Universitas Multi Data Palembang, 2026)
This study aims to determine the effect of Current Ratio (CR), Return on Assets (ROA), and Price to Earnings Ratio (PER) on the stock prices of companies in the technology sector listed on the Indonesia Stock Exchange for the 2021-2024 period. The research method used is quantitative. The population of this study is companies in the technology sector listed on the Indonesia Stock Exchange from 2021 to 2024. The sample in this study was obtained using a purposive sampling technique, totaling 26 companies in the technology sector. The data analysis technique used in this study is multiple linear regression. The results show that CR has no effect on stock prices, ROA does affect stock prices, and PER does affect stock prices.